Peculiarities of teaching coloronyms at different levels of studying a foreign language in higher education institutions - Solovyova, O. V.; Chorna, J. V.; Соловйова, Ольга Володимирівна; Чорна, Юлія Володимирівна (My University, 2024)
The article is devoted to the peculiarities of teaching coloronyms at different levels of foreign language learning in institutions of higher education. The article notes that color is an important element of nature that affects the result of a person’s perception of the external world. An interpretation of the color terms at the modern stage is provided. The definition of the term “coloronym” is given separately and it is stated that this definition is the most appropriate for conveying the emotional and mental state of a person, his character traits, social and cultural aspects of life. Three groups of coloronyms are studied by meaning: initial, extended and abstract meaning. The article indicates that most color adjectives are represented by nouns that mean food, materials, plants, animals, birds, and natural phenomena. It is noted that learning color vocabulary is not only about recognition; it’s a fun way to learn a language that offers opportunities to practice grammar, expand vocabulary and have meaningful conversations. Particular attention is paid to the peculiarities of learning coloronyms for students with different levels of knowledge of a foreign language. It suggests that students should be introduced to the pronunciation and spelling of the primary colors at an early stage and use visual materials such as color cards, real objects or even presentations to effectively associate the colors with their names. When working with intermediate students, it is necessary to expand their language skills while delving into the subtleties of color perception. At this stage of learning, it necessary to develop roleplaying scenarios that require students to solve problems related to color. At the advanced level students already have a good understanding of color vocabulary and can explore complex concepts related to color. At this stage, thought-provoking activities and discussions are needed that promote students’ critical thinking. The article indicates that when teaching the vocabulary of colors, the teacher must choose the most effective method according to the goals and take into account the level of language proficiency of the students and the tasks set before the students, especially if they are learning a foreign language for special purposes. Стаття присвячена особливостям навчання колоронімів на різних рівнях вивчення іноземної мови в закладах вищої освіти. У статті зазначається, що колір – це важливий елемент природи, який впливає на результат сприйняття людиною зовнішнього світу. Представлено аналіз термінів на позначення кольору на сучасному етапі. Окремо надано визначення терміну «колоронім» і зазначено, що це визначення є найбільш влучним для передачі емоційного та ментального стану людини, її рис характеру, соціальних і культурних аспектів життя. Досліджуються три групи колоронімів за значенням: початкове, розширене й абстрактне значення. У статті зазначається, що більшість прикметників на позначення кольору представлені іменниками, які означають продукти харчування, матеріали, рослини, тварин, птахів, природні явища. Зазначається, що навчання лексики кольорів – це не лише розпізнавання; це шлях до захоплюючого вивчення мови, який пропонує можливості практикувати граматику, розширювати словниковий запас і вести змістовні бесіди. Окрема увага приділена особливостям навчання колоронімів у студентів з різним рівнем знання іноземної мови в закладах вищої освіти. Вказується на те, що на початковому етапі потрібно ознайомити студентів з вимовою та написанням основних кольорів і використовувати візуальні матеріали, як-от кольорові картки, реальні об’єкти або навіть презентації, щоб ефективно пов’язувати кольори з їхніми назвами. У роботі зі студентами середнього рівня потрібно розширювати їхні мовні навички, водночас заглиблюватись у тонкощі сприйняття кольорів. На цьому етапі навчання потрібно розробити сценарії рольових ігор, які вимагають від студентів вирішення проблем, пов’язаних із кольором. На просунутому рівні студенти вже мають добре розуміння кольорової лексики та можуть досліджувати складні концепції, пов’язані з кольором. На цьому етапі потрібні заходи та дискусії, що спонукають до роздумів і сприяють критичному мисленню студентів. У статті зазначено, що під час навчання лексики кольорів викладачеві необхідно вибирати найбільш ефективний метод відповідно до поставлених цілей і брати до уваги рівень володіння мовою студентів і завдання, поставлені перед студентами, особливо якщо вони вивчають іноземну мову для спеціальних цілей.
Особливості навчання колоронімів на різних рівнях вивчення іноземної мови в закладах вищої освіти
Keywords: coloronyms; color-related concepts; color perception; color vocabulary; phenomenon of color; колороніми; концепції кольору; кольорова лексика; сприйняття кольору; феномен кольору